STUDI PEMANFAATAN CAMPURAN ZAT WARNA ALAMI DAN ASAM SITRAT SEBAGAI MORDAN TERHADAP KAYU JENIS AKASIA DENGAN METODE SIMULTAN MORDANTING - Bogoriani, Ni Wayan (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011)
Wood is one of several materials that is very useful to man kind, that even wood with low quality tends to be increasingly used. The great need for wood has been cousing wood of high quality is getting more difficult to obtain. To make wood of lows quality having high artistic value, a research to dye Acacia leucopholea wood with a mixture of natural dyes (Uncaria gambir-piper betle Linn leaves-Areca catechu seed) and 0.5 gram of citric acid in 100 mL water was conducted. To test its physical and chemical properties the treated wood 1% detergent solution was soaked in for 10 minute. The research conducted showed that the optimum mass proportion of the mixture for submertion of 10 minute with simultan mordanting method was 5.0:3.0:3.0 g (Uncaria gambir:piper betle Linn leaves:Areca catechu seed). The mixture resulted in Brown color and mean adsorption of 0.19 g of wood surface and showed highest durability against decolorization and mass loss test using 1% detergent solution.
Keywords: areca nut, betel leaf, gambier, citric acid